Marketing significance of local traditional food in the tourist hospitality offer (Vallis Aurea, 2022)
The global population is projected to reach nearly 10 billion by 2050, increasing the need for food from a variety of sources, and the preservation and sustainability of food crops and feed is more important than ever before. However, today suffi cient food supply is limited to existing resources. Additionally, the food expected to be needed by 2050 is only discussed in the context of quantity needed, not the quality and types that such increased demand will require. This will put enormous pressure on global economic systems, especially given the economic shift in consumption patterns that are slowly but surely moving towards the mass market. It is a fact that global requirements for food quality and hygiene, as well as technological advances, have helped in the distribution of a larger amount of food – from basic food components to quality meat, fi sh and poultry, to the convenience of snacks and drinks. The growing shift towards healthy, functional and/or organic foods consumed by consumers in many countries, and the increasing demand for traditional and ethnic foods outside their region, may be the driving force for innovating new approaches to feeding the growing world population in the future. In this context, governments, research institutions and the global food industry, especially those focused on ethnic and traditional food gathering and food production, are likely to develop strategies that will target more people.